Analisis Strategi Pengembangan Sub Sektor Tanaman Pangan Dalam Mendorong Pembangunan Ekonomi - A’ad Rizal Fauzi; Kurniyati Indahsari (Universitas Musamus,Merauke,Papua, 2022)
The purpose of this study was to identify the strategies of the food crop sub-sector development in Ngawi Regency and to determine its priorities. This study applied interactive qualitative analysis techniques and source triangulation that using primary and secondary data collected through depth interviews as well as documentation to identify the strategies. The strategies of the food crop sub-sector development were then analized using Analytical Hierarchy Process (AHP) to determine its priorities. It had been identified five strategies to develop the food crop sub-sector in Ngawi. The AHP calculation showed the production / cultivation (on farm) subsystem criteria as the the top criteria in strategy prioritization. Meanwhile, the first and the second prioritized strategies based on all criterias were increasing agricultural intensification through organic farming and empowering farmer groups collectively. The strategies of increasing partnerships with investors or owners of capital, increasing the procurement of post-harvest processing equipment and infrastructure, as well as optimizing the role of Bulog and implementing warehouse receipts were the last three priorities to be impemented.